STRATEGI KOMUNIKASI DALAM SOSIALISASI PENCEGAHAN THALASEMIA PADA YAYASAN THALASEMIA INDONESIA DI KOTA BANDUNG - Dwistin, Jennisa (2017)
Communication strategy research in health socialization is very important because communication strategy can determine the success of a communication program without exception health socialization. The process of behavior change in society is not something easy, so it needs to develop a proper communication strategy. The purpose of this study is to describe in detail about the communication strategies undertaken by health organizations in health dissemination. The communication strategy that will be described will consist of several stages: situation analysis, strategic design, development test, implementation and monitoring, and evaluation. The research was conducted at Thalassemia Foundation Indonesia in Bandung City. The research method used in this research is descriptive qualitative. Determination of research subjects conducted by purposive sampling. The results showed that in the situation analysis phase the foundation did so by identifying health problems, target audience, communication disorder, key influencer, work partner, and SWOT analysis. Strategic design is carried out with the strategy of selecting communicators, introducing socialization targets, presenting messages, selecting media, and determining effects. The foundation also conducts the development test phase well. Implementation of socialization is done if it is to get permission. Monitoring activities performed while socialization takes place. Stages of evaluation done by discussing the whole socialization activities from both the advantages and the disadvantages. Overall communication strategy is good however, the drawback lies in the use of media used